The Response of Accounting Study Programs in Indonesia to Issues of Changes in the Role of the Accounting Profession, Digitalization, and the Sustainability Era - Pradana, Bartolomeus Galih Visnhu (International Journal of Artificial Intelligence Research, 2024)
This study was conducted to identify the responses of academic programs in Indonesia to issues surrounding the changing roles of the accounting profession, digitalization, and the era of sustainability. The research employed both qualitative and quantitative approaches, utilizing data collection techniques such as surveys, documentation, observation, and in-depth interviews. There is a prevalent opinion that the accounting profession will diminish due to the substitution of human roles with robots because of digitalization. According to the findings from a Focus Group Discussion (FGD), participants revealed that technological advancements have significantly impacted accounting jobs. Financial statements can now be prepared using information technology applications and financial reporting software. These tools not only simplify and accelerate the work of accountants but also imply that the performance of accountants who do not utilize information technology could be adversely affected due to the demands for timeliness and accuracy in their work. The outcomes obtained from the FGD further disclosed that despite the rapid development of information technology, which greatly aids the work of accountants, a professional accountant must possess adequate knowledge of the fundamental principles of accounting. FGD participants concurred that information technology cannot replace the accounting profession. This is because the job of an accountant is not limited to just preparing financial reports for companies or organizations; rather, a professional accountant must also be capable of performing financial data analysis.